Water centric sustainable communities : planning, retrofitting, and building the next urban environment - Novotny, Vladimir, 1938- (John Wiley & Sons, 2010)
The current literature compartmentalizes the complex issue of water and wastewater into its discrete components; technology, planning, policy, construction, economics, etc. Considered from the perspective of sustainability, however, water in the urban environment must be approached as a single resource that can be continuously reused and recycled. From new construction to the retrofitting of existing systems, this book presents the case for a new urban relationship to water, one with a more sustainable connection to the environment and the hydrological cycle. Through case studies of successfully planned and built systems around the world, the book will educate the reader about the need for a new approach to urban water management, and make the case that these changes are not only possible but imperative. --From publisher's description.